2019
DOI: 10.1161/res.125.suppl_1.820
|View full text |Cite
|
Sign up to set email alerts
|

Abstract 820: Enoxaparin Reverses Ventricular Tachycardia and Torsades de Pointes in Rat Isolated Heart Model

Abstract: Introduction: Enoxaparin (Enox) is used in cardiovascular emergency and coronary angiography due to its effects on coagulation mechanisms. However, its effect on changing the structure of the exchange-inhibiting peptide present in the sodium-calcium exchanger, leading to the acceleration of its function and withdrawing calcium from the cell in overload situations could lead to a new therapeutic function, where the intracellular calcium overload would be deleterious, as in cardiac arrhythmias and my… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…It has also been suggested that this cardioprotective action of ADO mediated by cardiac A1R could occur in different physiological and pathological conditions, including CIR and cardiac pre- and post-ischemic conditioning [ 17 , 18 , 50 , 51 ]. Interestingly, heparin and LMWHs can prevent cardiac arrhythmias associated with sudden death caused by ventricular tachycardia, torsades de pointes , and ventricular fibrillation, and first- and second-degree AVB in animal CIR models, as well as in isolated rat atria [ 17 , 18 , 52 ]. Since Ca 2+ acts as a second intracellular messenger responsible for the regulation of various enzymes in cardiac cells, including AC, intracellular Ca 2+ overload may also indirectly promote myocardial injuries and lethal arrhythmias by disruption of the cardioprotective cAMP–ADO pathway [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has also been suggested that this cardioprotective action of ADO mediated by cardiac A1R could occur in different physiological and pathological conditions, including CIR and cardiac pre- and post-ischemic conditioning [ 17 , 18 , 50 , 51 ]. Interestingly, heparin and LMWHs can prevent cardiac arrhythmias associated with sudden death caused by ventricular tachycardia, torsades de pointes , and ventricular fibrillation, and first- and second-degree AVB in animal CIR models, as well as in isolated rat atria [ 17 , 18 , 52 ]. Since Ca 2+ acts as a second intracellular messenger responsible for the regulation of various enzymes in cardiac cells, including AC, intracellular Ca 2+ overload may also indirectly promote myocardial injuries and lethal arrhythmias by disruption of the cardioprotective cAMP–ADO pathway [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…The activation of cardiac β1-AR considerably increases intracellular cAMP levels in cardiac cells when extracellular Ca 2+ is decreased [ 25 , 47 , 53 ] or when the plasmalemmal NCX is inhibited in these cells [ 40 , 52 ]. cAMP, in turn, regulates c[Ca 2+ ] in cardiac cells and its dysfunction plays an important pathological role in the cardiac inflammation induced by AMI [ 27 , 54 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation